KARAKTERISTIK PENDERITA DIABETES MELLITUS TIPE II DENGAN TUBERKULOSIS PARU DI RSUD DR. PIRNGADI MEDAN TAHUN 2016 - Novelisa Lumbanraja; Rahayu Lubis; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Prevalence of communicable diseases and non-communicable diseases is double burden diseases in Indonesia. Diabetes mellitus (DM) is one of the non-communicable diseases that continues to increase in number and tend to be more at risk of pulmonary tuberculosis (TB) infections. The prevalence of type II DM with pulmonary TB in Indonesia by 2013 is 400 / 100,000 inhabitants. The purpose of this research is to know the characteristics of DM type II with pulmonary TB in RSUD Dr. Pirngadi Medan in 2016. Research is descriptive with case series design. Population is all data of DM type II patients with pulmonary tuberculosis with many sample that is 112 patient. Univariate data were analyzed descriptively while bivariate data were analyzed using Chi-Square test.           The results showed the highest proportion of patients with type II DM and pulmonary tuberculosis were age group ≥ 40 years (92%), male (60,7%), Bataknese (63,4%), Islam (60,7%), SMA (equal to 76.8%), entrepreneur (38.4%), Medan City (58%), HbA1C (70.5%), HbA1C ≥ 7% (uncontrolled) %), Smear positive pulmonary TB (82.1%), new cases (37.5%) and relapse cases (37.5%), heart and blood vessel disorders (36.6%), Oral Hypoglycemic Drugs OHO) (64.3%), BPJS / ASKES / KIS (90.2%), becoming outpatient / PBJ (83%). There was no significant difference between the proportion of HbA1C levels based on the proportion of type II DM treatment (p = 1,000) and there was a significant difference between the proportion of HbA1C levels based on the proportion of sputum microscopic pulmonary examination results (0.0001).               The results showed a difference between the proportion of HbA1C levels based on the proportion of sputum microscopy pulmonary examination results. It is desirable for the hospital to check HbA1C levels for DM type II patients with pulmonary tuberculosis and to the patient to be treated immediately and prevent transmission to others and is expected to perform routine HbA1C examination.Keywords: Type 2 DM, Pulmonary TB, characteristic of the patient